Affordable Chemistry for children (Research, Society and Development, 2020)
Taking into account the development of scientific thinking since the time that students are children, this work presents the results of an extension project that was elaborated with the objective of contributing to the improvement of the quality of chemistry teaching. The project had the elaboration of a didactic material and an experimental kit developed with materials of low cost and easy access, being delivered to the State Schools of Bambuí and region. According to the results presented, those involved in the project understood the children's notions and were able to verify that their previous knowledge contributed to the construction of the teaching-learning process, and satisfactory results were presented in the responses of the activities of the didactic material as well as in the explanation of the experiences conducted at the Science Fairs, which were presented in the schools contemplated. The project motivated students to conceive chemistry as a practical science and applicable in everyday situations. The objectives coincided with the strategic plan involving the IFMG- Campus Bambuí, which links the relationship between learning to do and do to learn, with the expanded extension for the formation of critical citizens who could contribute to chemical knowledge built continuously